Hypoxia inducible factors 1alpha and 2alpha are associated with VEGF expression and angiogenesis in gallbladder carcinomas. - Giatromanolaki, A; Sivridis, E; Simopoulos, C; Polychronidis, A; Gatter, K; Harris, A; Koukourakis, M (2006)
AIMS: To investigate the significance of the hypoxia inducible factors HIF-1alpha and HIF-2alpha in gallbladder adenocarcinomas and their relation to angiogenesis and to the expression of VEGF, an angiogenic factor transcriptionally regulated by HIFalphas. METHODS: HIF-1alpha and 2alpha expression was assessed immunohistochemically in 60 patients with early gallbladder adenocarcinomas, treated with surgery alone. In addition, the vascular density (VD) and the expression of the angiogenic factors VEGF and thymidine phosphorylase (TP) were examined. The results were correlated with clinico-pathological features and prognosis. RESULTS: Overexpression of HIF-1alpha and 2alpha was significantly associated with increased tumor angiogenesis and VEGF expression, while HIF-2alpha was linked with upregulation of TP. None of these factors were associated with T-stage and tumor grade. Although HIFs did not relate significantly with prognosis, patients with HIF-1/2 expression who failed to switch-on VEGF or intratumoral angiogenesis had a favorable outcome. CONCLUSION: Hypoxia inducible factors are upregulated in a large proportion of gallbladder adenocarcinomas, a feature strongly related to increased expression of VEGF and intensified angiogenesis.